Insights into the interaction of negative allosteric modulators with the metabotropic glutamate receptor 5: Discovery and computational modeling of a new series of ligands with nanomolar affinity. Issue 13 (1st July 2015) - Anighoro, Andrew; Graziani, Davide; Bettinelli, Ilaria; Cilia, Antonio; De Toma, Carlo; Longhi, Matteo; Mangiarotti, Fabio; Menegon, Sergio; Pirona, Lorenza; Poggesi, Elena; Riva, Carlo; Rastelli, Giulio
Graphical abstract: Abstract: Metabotropic glutamate receptor 5 (mGlu5 ) is a biological target implicated in major neurological and psychiatric disorders. In the present study, we have investigated structural determinants of the interaction of negative allosteric modulators (NAMs) with the seven-transmembrane (7TM) domain of mGlu5 . A homology model of the 7TM receptor domain built on the crystal structure of the mGlu1 template was obtained, and the binding modes of known NAMs, namely MPEP and fenobam, were investigated by docking and molecular dynamics simulations. The results were validated by comparison with mutagenesis data available in the literature for these two ligands, and subsequently corroborated by the recently described mGlu5 crystal structure. Moreover, a new series of NAMs was synthesized and tested, providing compounds with nanomolar affinity. Several structural modifications were sequentially introduced with the aim of identifying structural features important for receptor binding. The synthesized NAMs were docked in the validated homology model and binding modes were used to interpret and discuss structure–activity relationships within this new series of compounds. Finally, the models of the interaction of NAMs with mGlu5 were extended to include important non-aryl alkyne mGlu5 NAMs taken from the literature. Overall, the results provide useful insights into the molecular interaction of negative allosteric modulators with mGlu5 and may facilitate the design of new modulators for this class of receptors.